Perspectiva de la mezcla de marketing para la comercialización de queso zarumeño. - Villavicencio, Maria Fernanda; Zaruma Jiménez, John Kelvin; Gamboa Salcedo, Rosalva Beatriz; Sornoza Guerra, Mónica Andreina (My University, 2021)
To analyze the consumer behavior of Zarumeño dairy products in order to suggest marketing mix strategies that contribute efficiently to the commercialization of Zarumeño cheese in the cantons of the lower part of the province of El Oro. Research with quantitative approach. Probabilistic sampling stratified by proportional allocation, with a sample of 383 families surveyed. The analysis of the information was carried out with the SPSS statistical program. 62.1% of the population consumes dairy products produced in the canton of Zaruma, 86.1% of which consume Zaruma cheese. The high percentage of consumption is evidenced by the existence of a latent demand, which is often unsatisfied due to difficult access to the product and the absence of sanitary registration. The marketing mix strategies suggested in the study, will allow strengthening the positioning of the product, its competitive advantage and strengthen adequate marketing, distribution and promotion. This study was conducted within the framework of the community outreach project 06-VS-2018, whose beneficiaries are dairy producers in the province of El Oro.
Analizar el comportamiento del consumidor de productos lácteos zarumeños, para sugerir estrategias de marketing mix, que contribuyan de manera eficiente en la comercialización de queso Zarumeño, en los cantones de la parte baja de la provincia de El Oro. Investigación con enfoque cuantitativo. Muestreo probabilístico estratificado por afijación proporcional, con una muestra de 383 familias encuestadas. El análisis de la información se realizó en el programa estadístico SPSS.El 62.1% de la población consume lácteos producidos en el cantón Zaruma, de ellos el 86.1% consumen queso zarumeño; logrando evidenciar el alto porcentaje de consumo, se considera la existencia de una demanda latente, que en muchas ocasiones es insatisfecha por el difícil acceso al producto y ausencia de registro sanitario. Las estrategias de marketing mix sugeridas en el estudio, permitirán fortalecer el posicionamiento del producto, su ventaja competitiva y fortalecer la comercialización, distribución y promoción adecuadas. El presente estudio fue realizado en el marco del proyecto de vinculación con la comunidad 06-VS-2018, cuyos beneficiarios son los productores de lácteos de la provincia de El Oro.
Keywords: MARKETING MIX; POSICIONAMIENTO; COMERCIALIZACIÓN; DISTRIBUCIÓN; LÁCTEOS